TATHWIR MADDAH MAHARAH AL KALAM ALA ASAS TANDUR FII MARKAZ TARQIYATI AL LUGHAH BI JAMIATI SULTHAN SYARIF QASIM AL ISLAMIYAH AL HUKUMIYAH RIAU - Khoirul Huda (Jurnal Alsinatuna, 2016)
Ideally, students of Arabic Education Program can speak Arabic fluently. In fact, there are some students of UIN Suska Riau lack speaking skill in Arabic that may caused by lack of practice in their daily communication. Therefore, in this study, the researcher wants to develop a new teaching method as a solution in improving students’ speaking skill. This study uses Research and Development method which focused on the development of a new teaching method called TANDUR. The development of this method is done by analyzing the needs of students, developing the components of the method, presenting it in front of experts, having a field testing, and revising it based on the advice given by the experts. The result of this study shows that Tandur method brings positive effect in improving students’ Arabic speaking skill.